2021
DOI: 10.1371/journal.pone.0252101
|View full text |Cite
|
Sign up to set email alerts
|

Lived experiences of older adults during the first COVID-19 lockdown: A qualitative study

Abstract: Background and aim Public health measures used to mitigate the COVID-19 epidemic may have unintended, detrimental consequences particularly on older adults, whose voices and perspectives are often silent or silenced. The aim of this study was to explore the lived experiences of individuals aged 64 or older during the first COVID-19 lockdown. Methods We conducted a qualitative study in a convenience sample of 19 older adults (aged 64+) living at home in the Italian-speaking region of Switzerland during the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
61
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 36 publications
(42 reference statements)
2
61
0
1
Order By: Relevance
“…Many participants expressed disappointment and anger towards individuals who did not follow the prescribed safety measures, with a common focus on younger generations. This tension with noncompliant citizens and youth aligns with the aforementioned qualitative study in southern Switzerland, which reported anger towards those who did not respect COVID-19 prevention measures as well as the institutions that were not enforcing the rules [ 19 ]. This cohort of older adults also expressed anger towards the youth, perceiving a sense of ageism from this generation and a disregard for the lives of vulnerable persons [ 19 ].…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Many participants expressed disappointment and anger towards individuals who did not follow the prescribed safety measures, with a common focus on younger generations. This tension with noncompliant citizens and youth aligns with the aforementioned qualitative study in southern Switzerland, which reported anger towards those who did not respect COVID-19 prevention measures as well as the institutions that were not enforcing the rules [ 19 ]. This cohort of older adults also expressed anger towards the youth, perceiving a sense of ageism from this generation and a disregard for the lives of vulnerable persons [ 19 ].…”
Section: Discussionmentioning
confidence: 56%
“…This tension with noncompliant citizens and youth aligns with the aforementioned qualitative study in southern Switzerland, which reported anger towards those who did not respect COVID-19 prevention measures as well as the institutions that were not enforcing the rules [ 19 ]. This cohort of older adults also expressed anger towards the youth, perceiving a sense of ageism from this generation and a disregard for the lives of vulnerable persons [ 19 ]. In the current sample, greater concern for others’ wellbeing was emphasized among older adults, which is aligned with the notion that aging is associated with greater altruism [ 20 ].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The results may not be generalizable to a wider population. Furthermore, the lack of face-to-face interviews might have prevented participants from freely expressing their possible frustrations during the pandemic [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it is the summation of the combined results of a survey conducted by local governments operating Community Care Pilot Projects implemented by the Korean government. Hence, this study provides evidence for effective implementation of TKM community care provision policy [ 27 , 28 ]. Remarkably, several TKM institutions ( n = 136) participated in this project, providing a TKM community home care program for a total of 598 people.…”
Section: Discussionmentioning
confidence: 99%